Beyond the Laws: Analysing Police Intervention Strategies for Handling Domestic Violence in Ghana and Nigeria - Abena Asefuaba Yalley (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
Substantial research has demonstrated that the police are critical agents in dealing with the problem of DV and reducing its overall prevalence. The passage of the DV laws in Ghana and Nigeria made the police the primary agency to respond to DV: however, there is limited research on how police handle domestic violence in the two countries. This study, therefore, critically interrogated police intervention strategies in handling DV and their effectiveness in Ghana and Nigeria. In-depth interviews were conducted with 100 female victims of DV who have utilized police services and 30 police officers who handle DV cases. In addition, ethnographic observations were made in the police stations. The study found that arrest and detention, prosecution at the law court and the use of caution letters are the major conventional strategies used by the Ghana and Nigeria police to handle domestic violence. The two police institutions also adopted culturally sensitive approaches such as mediation, invitation letters and the use of minor punishment to deter offenders and potential offenders. There were a few variations in how the two police institutions handled domestic violence. The Ghana police utilized invisible arrest to preserve family relationships while the Nigeria police adopted naming and shaming of perpetrators to deter the public. The effectiveness of the interventions was mixed, depending on cultural acceptability, victims’ needs and impact on perpetrators. Police interventions emphasized punishments, and this often brought swift changes in offenders’ behavior but the changes were not sustainable.